Comparison of the Effectiveness of Microteaching and School Environmental Introduction (PLP 2) in Developing Teaching Skills for Biology Education Students - Audrey Louise Makatita; Ayu Christine Rahaweman; Riwa Rambu Hada Enda; Mia Fransiska M. Dimu (Jurnal Penelitian Pendidikan IPA, 2024)
The research presented a comparison analysis of the effectiveness of microteaching and PLP 2 in developing teaching skills for biology education students. Microteaching, a commonly used method in higher education, involves simulated teaching sessions where students receive feedback from peers and instructors. On the other hand, PLP 2 offers practical teaching experience in a school environment, providing real challenges and interaction with students in the classroom. This research evaluates and compares how both methods contribute to improving teaching competencies. The main findings indicate that while microteaching focuses on pedagogical techniques and classroom management, PLP 2 emphasizes adaptability to various learning environments and student engagement strategies. The study concludes that integrating both approaches into teacher education programs can better prepare aspiring educators with the comprehensive skills to teach in diverse educational contexts